2001
DOI: 10.1007/3-540-45468-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Periaxial Rotation Measurement for Aligning Fractured Femur Fragments: Method and Preliminary Results

Abstract: We describe a new computer-based method for periaxial rotation measurement of healthy and fractured femurs during closed femoral fracture reduction surgery from CT. The method provides a comparative quantitative measure to align the distal and proximal femur fragments based on periaxial rotation. We define periaxial rotation in terms of patient-specific bone features and describe an algorithm for automatically extracting these features from the CT. The algorthm extracts condyle landmarks and neck axis of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…[7][8][9][10] Ron et al reported a computerized bone reconstruction system, but it was restricted to simple two-fragment fractures. 11 This paper extends recently developed techniques from the computer vision and computer graphics community for reconstructing broken archaeological artifacts [12][13][14] for application to reconstructing highly fragmented bone fractures. While some of these techniques are directly applicable to bone reconstruction, there are many new challenges.…”
Section: Purposementioning
confidence: 88%
“…[7][8][9][10] Ron et al reported a computerized bone reconstruction system, but it was restricted to simple two-fragment fractures. 11 This paper extends recently developed techniques from the computer vision and computer graphics community for reconstructing broken archaeological artifacts [12][13][14] for application to reconstructing highly fragmented bone fractures. While some of these techniques are directly applicable to bone reconstruction, there are many new challenges.…”
Section: Purposementioning
confidence: 88%
“…Yet, these methods are designed to work with materials such as pottery and stone, which have different fracture mechanics than bone, they rely on highly-accurate laser-scan data, and they restrict their matching assumptions to have a 1-to-1 correspondence, i.e., solutions for these systems require that each fragment fracture surface matches with only one other fragment fracture surface. Early efforts toward computer-aided bone fracture reconstruction included a system for reconstructing a simple two-fragment bone fracture [4]. Completely interactive approaches for bone fragment manipulation and alignment have since been proposed by Scheuering et al [5] and by Harders et al [6].…”
Section: Contribution Of This Workmentioning
confidence: 99%
“…Research on bone reconstruction is generally limited to simple fractures from a small number of fragments [ 11 ]. The recent emergence of 3D technologies has increased the potential to investigate personalized treatment of fractures [ 12 , 13 ], to propose preoperative plans [ 14 ], but also to develop customized treatment solutions in cases of simple fractures [ 15 ] or complex ones [ 16 , 17 ], specific instrumentation, osteointegrated implants for traumatology and orthopedics [ 18 ].…”
Section: Introductionmentioning
confidence: 99%